Erythropoiesis in humans exposed to severe altitude hypoxia - Antezana, Ana María; Souberbielle, Jean Claude; Le Trong, Jean Louis; Richalet, Jean Paul (Acta Andina, 2025)
Some of the factors involved in the control of altitude polycythemia were studied in ten subjects (4 women, 6 men) exposed for 3 weeks 10 extreme altitude (6542 m). Blood was withdrawn in normoxia (N), after one (H1), two (H2) and three (H3) weeks at 6542 m. for the measurement of serum erythropoietin (EPO, mU/mJ), blood hemoglobin (Hb, g/dl), hematocrit (Ht,%), intra erythrocyte folate (FOL, ug/l) and plasma ferritin (FER, ug/l) concentrations. Renal absolute proximal reabsorption rate (APR) were measured by the lithium clearance method, in N and H2 conditions. After an initial sharp increase in EPO (N: 8 ± 2. H1: 302 ± 282, mean± S.D.), EPO decreased at H2 (161 ± 151) and H3 ( 174 ± 212). Ht and Hb increased from N (43 ± 3; 13.8 ± 0.7) to H1 (51 ± 6, 15.7 ± 2.3) and H2 (53 ± 7, 16.1 ± 2.3) and then decreased from H2 to H3 (49 ± 7, 15.0 ± 2.5). lncrease in EPO at H1 varied from 3 to 134-fold among individuals. Two women showed a large increase in EPO without increase in Hb. FER showed a marked decrease in H1 (8. 1 ± 4.9) and H3 (9.2 ± 3.8) as compared to N (28.0 ± 24.5). Hb was positively related to FER in hypoxia. Iron intake in food was markedly decreased during the 2 weeks of ascent, before arriving at 6542 m. EPO was inversely related to Ca02 and positively related to APR. The increase in Hb at H1 may have restored the oxygen availability in the kidneys and reduced the formation of EPO. The decrease in Hb from H2 to H3, in spite of a high EPO, may be due to a chronically reduced substrate (iron) availability, as suggested by the decrease in FER favoured by a low iron in take. We conclude that there is a great interindividual variability in erythropoiesis response to EPO in hypoxia. Factors involved in the modulation of this response include nutritional and sex differences, iron stores and tubular function that determines O2 supply to renal sensors responsible for EPO secretion.